2013
DOI: 10.1074/jbc.m113.473728
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dissection of the Binding Contributions of Ligand Lysines of the Receptor-associated Protein (RAP) to the Low Density Lipoprotein Receptor-related Protein (LRP1)

Abstract: Background: Only small effects on affinity are seen for seemingly critical lysines of LRP1 ligand RAP. Results: Lysines act in pairs and fully account for overall affinity to LRP1. Mutagenesis reduces binding up to 100,000-fold. Conclusion: Two pairs of paired lysine interactions can give high affinity binding of protein ligands to LRP1. Significance: Rules for identifying high affinity receptor binding sites are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
(32 reference statements)
4
27
0
Order By: Relevance
“…This close agreement suggests that we have not only identified basic residues in PAI-1 that are important for binding to LRP1 but have shown that their binding contributions quantitatively account for all of the binding energy. In a similar way, we previously showed that engagement of four lysines in RAP D3 accounted fully for the high affinity interaction with CR56 (21). It is striking however, that, although the mutations reported here resulted in extremely large increases in K d values, the same mutations reported elsewhere had mostly negligible effects (18).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This close agreement suggests that we have not only identified basic residues in PAI-1 that are important for binding to LRP1 but have shown that their binding contributions quantitatively account for all of the binding energy. In a similar way, we previously showed that engagement of four lysines in RAP D3 accounted fully for the high affinity interaction with CR56 (21). It is striking however, that, although the mutations reported here resulted in extremely large increases in K d values, the same mutations reported elsewhere had mostly negligible effects (18).…”
Section: Discussionmentioning
confidence: 64%
“…The most disconcerting is that basic residues identified as being involved in binding result in no more that an 11-fold increase in K d when mutated and mostly much less, whereas the affinity of PAI-1 for LRP1 is in the low nanomolar region. Such very small effects are not expected if basic residues are the dominant contributors to overall affinity, which has been quantitatively shown to be the case for the RAP D3/CR56 interaction (21) and for model compounds binding to individual CR domains (22). The second problem is that there is no consensus on which basic residues constitute the binding site, with some residues identified as being important in one study (13,19,20) and having little or no effect when mutated in another study (18).…”
mentioning
confidence: 94%
“…Therefore, hydrophobic residues located in the vicinity of the lysine residue may determine whether a lysine residue is a hot spot or not. Alternatively, the presence of a second proximal charge near the lysine residue, or perhaps even repulsive charges from amino acid residues surrounding the lysine residue, may determine specificity (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these data, arginine residues also do not take over lysine residues in the high-affinity interactions of RAP-D1 (Lys 143 and Lys 146 ) with the LDL receptor (16). In a recent elegant study, Dolmer et al (17) established that lysine residues are the sole contributors to binding of RAP-D3 to an LRP1 fragment containing two CR domains and that pairs of lysine residues ensure high-affinity interaction in an additive rather than a synergistic manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation